Cardosin A endocytosis mediated by integrin leads to lysosome leakage and apoptosis of epithelial cells. Issue 6 (15th March 2019) - Wu, Hao; Castanheira, Pedro; Faro, Carlos; Tang, Jordan
Abstract: Cardosin A is an aspartic protease present in large amount in the pistils of cardoon flowers. This protease is known to contain an ‐Arg‐Gly‐Asp‐ (RGD) motif located on the molecular surface. In this study, we found that isolated recombinant cardosin A attached to human epithelial cells A549, mediated by the binding of its RGD motif to cell surface integrins. The cell bound cardosin A was internalized to endosomes and lysosomes and triggered the permeability of lysosomal membrane leading to apoptosis of the epithelial cells. These events are identical to those observed for three RGD‐containing aspartic proteases, Saps 4‐6, secreted by Candida albicans . Such a process, which has been called the Trojan Horse mechanism, is believed to benefit the invasion of C. albican into the epithelium of the host. The location of the RGD motifs of cardosin A and Saps 4‐6 are on the opposite ends of the homologous three‐dimensional structures, suggesting that the Trojan Horse mechanism is insensitive to the RGD position. Current finding also suggests that cardosin A may have a defensive function against the ingestion of cardoon flowers by human, insects, and other herbivores.